(3GdeaGgje hGdeeGQSGJ eOYeI HCSFdI hMGdGJ JWHjbjIs - (3djfOI(B, (3QbGes ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2021)
(3jVe gPG GdcJGH GKfi YTQ aUdG, JYQV GdaUd GdChd efg Edi WHjYI hJWhQ hXjaI GdehGQO GdHTQjI, hJfGhd GdaUd GdKGfj COhGQ GOGQI GdehGQO GdHTQjI hJfXjegG hGdCaQGO GdYGedjf ajgG aj Mjf LGAJ GdaUhd GdJSY dJJYeb aj CfTWI EOGQI GdehGQO GdHTQjI GdeJeKdI aj JMdjd hhUa hJhUja efGUH GdYed, JNWjW GdehGQO GdHTQjI, GdJhXja, GdGSJbWGH, GdGNJjGQ, GdJYjjf, GdGOeGL, Jbjje COGA GdehGQO GdHTQjI, fXGe GdCLhQ hGdMhGaR, GdJchjf hJWhjQ GdegGQGJ, GOGQI GdeSGQGJ GdegfjI, MaX GdUMI hGdCef, GdNOeGJ hGdeRGjG GdGLJeGYjI, hLGA GdaUd GdCNjQ ef GdcJGH djJfGhd EOGQI GdehGQO GdHTQjI aj GdeDSSGJ GdUZjQI eY GdYde Cf cd aUd ef gPg GdaUhd cGf eJHhYG HCSFdI JMdjdjI hCNQi JWHjbjI eJeKdI aj OQGSI MGdGJ JeJ eYGdLJgG aj fgGjI GdcJGH(B.s
(3eQGLY U(B.206s
Keywords: (3EOGQI GdCaQGOs; (3EOGQI GdehGQO GdHTQjIs